Analysis of Company Performance in the Coal Subsector from the Sustainability Development Goals’s Perspective in Indonesia - Anggraini, Winda Ayu; Pradani, Tiara; Nanda, Ulfa Luthfia (AIBPM Publisher, 2023)
Environmental issues have been under discussion for the last few years in various countries. The world, including Indonesia, has become more polluted and stakeholders are busy looking for solutions to maintain biodiversity. This research analyzes the performance of coal subsector companies listed on the Indonesian Stock Exchange from the perspective of sustainability development goals. The population in this study is 22 coal subsector companies, which the coal subsector is the largest mining sector in Indonesia and it contributes to several causes of environmental problems. The research method is carried out by scoring 17 indices of sustainability development goals. Data was taken from sustainability reports in the period 2021 and 2022. In-depth data analysis was carried out to correlate the score results with the indicators disclosed in the company's sustainability report. The results explain that the disclosure of sustainability reports containing 17 sustainability development goals indices has fluctuated in two periods between companies. A small number of companies still do not provide information regarding their sustainability programs and others do not fully disclose the 17 indices. The results of this research are expected to become a benchmark for stakeholders to evaluate mining sector companies in their sustainable environmental management attempts.